Noncontrast chest computed tomographic imaging of obesity and the metabolic syndrome: Part II noncardiovascular findings - Nattenmüller, Johanna; Schlett, Christopher L.; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver (Journal of thoracic imaging, 2019)
The purpose of this review article is to acquaint the reader with the current state of the art for the noncardiovascular imaging biomarkers of metabolic syndrome found on noncontrast computed tomography (NCCT) of the chest and their prognostic significance. Routine chest NCCT includes quantitative information with regard to tissue density and organ volumes in the neck, chest, and upper abdomen. The specific imaging biomarkers that may be seen in association with metabolic syndrome include low thyroid iodine organification, hepatic steatosis, sarcopenia (muscle volume and density), demineralization of the thoracic and upper lumbar vertebral bodies, loss of axial skeletal muscle mass, premature lung inflammation, and an increased deposition of subcutaneous and visceral fat. These easily identified imaging biomarkers can have prognostic implications, which include nonalcoholic steatohepatitis, cirrhosis, hypothyroidism, early lung fibrosis with interstitial abnormalities, sarcopenia, and osteoporotic thoracic and lumbar spine vertebral body compression fractures. NCCT examinations of the chest have the opportunity to become an important imaging tool for outcomes research.